The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.31933/dijms.v2i3.702
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Citizenship Behaviour That Mediated Those Influence of Transformational Leadership and Organizational Culture Towards Employee Performance at Xyz Organization

Abstract: Main purpose of this research was to explored An organizational citizenship behaviour's influenced that mediate the impact from transformational leadership and organizational culture towards employee performance at XYZ organizational. Research population was all employees from XYZ Organization, amounting to 113 employees. Sample method by non-probability sampling with saturated sampling as sampling technique so respondents chosen was 113 respondents. Data analysis method in this research used Structural Equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…KHMI in order to improve the performance of its employees. The results of this study are in line with the research of Rahmawaty & Lo (2021) and Dewi et al, (2018) who found that transformational leadership has an affect on employee performance. If it is associated with the results of the correlation matrix between dimensions, it can be seen that the dimensions of inspirational motivation and intellectual stimulation in transformational leadership have a very strong correlation with the dimensions of work quality on the employee performance variable.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…KHMI in order to improve the performance of its employees. The results of this study are in line with the research of Rahmawaty & Lo (2021) and Dewi et al, (2018) who found that transformational leadership has an affect on employee performance. If it is associated with the results of the correlation matrix between dimensions, it can be seen that the dimensions of inspirational motivation and intellectual stimulation in transformational leadership have a very strong correlation with the dimensions of work quality on the employee performance variable.…”
Section: Discussionsupporting
confidence: 92%
“…Wirawan in Kaswan (2017) defines that organizational culture acts as a guide in controlling and carrying out work activities for each member in the organization, therefore it will increase work motivation. Rahmawaty & Lo (2021) state that organizational culture is the most core part of an organization, which has the power to influence the success or failure of an organization. The organizational culture which applied by employees will be able to increase their work motivation (Rahmawaty & Lo, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations